Evaluation of Uterocervical Angle and Cervical Length as Predictors of Spontaneous Preterm Birth - Pramod Kumar Singh; Resham Srivastava; Ishan Kumar; Sangeeta Rai; Saurabh Pandey; Ram C. Shukla; Ashish Verma (Indian Journal of Radiology and Imaging, 2022)
Aim The aim of this article was to evaluate uterocervical angle (UCA) and cervical length (CL) measured at 16 to 24 weeks of gestation using transvaginal sonography (TVS) as predictors of spontaneous preterm birth. Methods In this prospective study, TVS was performed in 159 primigravidas with a singleton, uncomplicated pregnancy at 16 to 24 weeks of gestation to measure the anterior UCA and CL. All the cases were followed until labor to document gestational age at delivery. Results The risk of spontaneous preterm birth was higher in women with obtuse UCA (>95 degrees) with sensitivity of 86.7%, specificity of 93.0%, positive predictive value of 83.0%, negative predictive value of 94.6%, and p-value of <0.001. The difference between the means was statistically significant (p-value < 0.001). UCAs ≥105degrees and 95 to 105 degrees were found to be significantly associated with spontaneous preterm births at <34 weeks and 34 to 37 weeks, respectively. CL <2.5 cm was found to predict spontaneous preterm births at <37 weeks with sensitivity of 31.1%, specificity of 95.6%, and p-value of <0.001. UCA was found to be a better predictor of spontaneous preterm birth with a higher coefficient of variation (56.4%) when compared with CL (16.9%). Conclusions UCA proved to be a novel ultrasound parameter that can serve as a better predictor of spontaneous preterm births in comparison to CL. A strong correlation exists between obtuse UCA and a risk of spontaneous preterm birth.